152k views
1 vote
Simplify the expression: (3 − 4i) + (7 − 6i).

User Dimid
by
4.7k points

2 Answers

1 vote

Answer:

10-10i

Step-by-step explanation:

Isolate i on one side of the equation.

(3-4i)+(7-6i)

DISTRIBUTIVE PROPERTY:

A(B+C)=AB+AC

A(B-C)=AB-AC

(A+BI)±(C+DI)=(A±C)+(B±D)I

(3+7)+(-4-6)i (Solve.)

7+3=10

-4-6i=-10

10-10i

Therefore, the final answer is 10-10i.

User Akeeseth
by
4.8k points
4 votes
=10-10i
Step-by-step explanation:
3-4i+7-6i
(Add 3 and 7)
(Add -4i and -6i)
Put together
10-10i
User Boon
by
5.1k points